China's financial markets : an insider's guide to how the markets work - Neftci, Salih N.; Ménager-Xu, Michelle Yuan (Amsterdam ; Boston : Elsevier, 2007)
The book brings together a collection of Chinese insiders who are experts in their respective industries. These experts provide a detailed description of the banking system, the money, equity, futures, FX, and bond markets, the insurance sector, the mortgage market and mortgage instruments, and the regulators. Readers will learn how each of these financial sectors operates, how the government, regulators, and the central bank are involved, each sector s history, size and projected growth, an analysis of its current situation and discussion of future trends, the major players, and how the game is played. This is a must-read book for financial success in this emerging market.
Title on CD-ROM: China's financial market regulations
Includes bibliographical references and index.
lje 13/07/16
Keywords: Finance; Financial services industry; Capital market